First report of Erysiphe elevata causing powdery mildew on Catalpa bignonioides in Montenegro - LATINOVIĆ, Jelena; LATINOVIĆ, Nedeljko; JAKŠE, Jernej; RADIŠEK, Sebastjan (Phytopathologia Mediterranea, 2019)
The first record of powdery mildew caused by Erysiphe elevata in Montenegro is presented in this paper. The fungus was detected on leaves, fruits and flowers of Catalpa bignonioides, causing severe disease of some trees, and was identified on the basis of morphological and molecular characteristics. In pathogenicity tests, inoculation of leaves of healthy young plants of southern catalpa resulted in typical powdery mildew symptoms.